2002
DOI: 10.1161/01.hyp.0000033974.57407.82
|View full text |Cite
|
Sign up to set email alerts
|

Association of eNOS Glu298Asp Polymorphism With End-Stage Renal Disease

Abstract: Abstract-Nitric oxide (NO) derived from endothelial cells is profoundly related to the maintenance of physiological vascular tone. Impairment of endothelial NO generation brought about by gene polymorphism is considered the major deterioration factor for progressive renal disease, including diabetic nephropathy. The present study aimed to elucidate the Glu298Asp polymorphism of endothelial NO synthase (eNOS) in patients with end-stage renal disease (ESRD) and its role as a predisposing factor for cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
6
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(114 citation statements)
references
References 33 publications
(39 reference statements)
4
97
6
7
Order By: Relevance
“…One of the first indications that genes within chromosome 7q35 (including NOS3) could influence genetic susceptibility to DN came from the nonparametric linkage study in Pima Indians [16]. Several positive associations of some of the numerous NOS3 SNPs with renal disease were documented in type 1 [41] and type 2 diabetes [42], as well as in non-diabetic subjects [43,44], while other studies did not find an association [45]. The two 'set-associated' SNPs in our study-silent substitution 774C/T in exon 6 altering the third base of the codon (both encoding an Asp) and non-synonymous substitution 894G/ T alleles in exon 7 (probably not functional though since the resulting amino acid difference at position 298 Glu to Asp in the oxygenase domain is a conservative one)-are the most probably neutral genetic markers of a yet unidentified functional NOS3 or neighbouring gene polymorphism in a linkage disequilibrium with the two SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…One of the first indications that genes within chromosome 7q35 (including NOS3) could influence genetic susceptibility to DN came from the nonparametric linkage study in Pima Indians [16]. Several positive associations of some of the numerous NOS3 SNPs with renal disease were documented in type 1 [41] and type 2 diabetes [42], as well as in non-diabetic subjects [43,44], while other studies did not find an association [45]. The two 'set-associated' SNPs in our study-silent substitution 774C/T in exon 6 altering the third base of the codon (both encoding an Asp) and non-synonymous substitution 894G/ T alleles in exon 7 (probably not functional though since the resulting amino acid difference at position 298 Glu to Asp in the oxygenase domain is a conservative one)-are the most probably neutral genetic markers of a yet unidentified functional NOS3 or neighbouring gene polymorphism in a linkage disequilibrium with the two SNPs.…”
Section: Discussionmentioning
confidence: 99%
“…Failure of this adaptation is thought to result in increased blood pressure, proteinuria, and wide-spread endothelial dysfunction (classical pre-eclampsia), arteriolar contraction, ischaemia of the decidua basalis, necrosis and haemorrhage (classical placental abruption). Although reduced NO bio-availability has already been reported in eNOS Asp298 homozygous individuals, there remains controversy about the interpretation of these findings (Fairchild et al 2001;Noiri et al 2002;Serrano et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…They found a significant association with diabetic nephropathy in type 2 diabetes when they examined the 242C/T polymorphism accompanied with the receptor for advanced glycation end products (RAGE) gene 1704G/T polymorphism. It is likely that other genetic factors in addition to RAGE polymorphisms, such as nitric oxide synthetase, methylenetetrahydrofolate reductase, peroxisome proliferator-activated receptor cÀ2, and aldose reductase gene polymorphisms may also contribute predisposing factors to diabetic nephropathy (Caramori et al 2003;Noiri et al 2000Noiri et al , 2002Zhao et al 2004b). Hodgkinson et al 2003) showed an association of the 242C/T polymorphism with diabetic nephropathy in type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%